Analysis of Learning Quality through Video-Based eLMA Learning in Department Mathematics of Education - Ika Krisdiana; Wasilatul Murtafiah; Titin Masfingatin; Reza Kusuma Setyansyah; Vera Dewi Susanti (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2021)
The use of ICT became important after the government through a circular letter from the Minister of Education and Culture regarding the call for the implementation of online learning to prevent the transmission of Covid-19. Each educational institution including Universities PGRI Madiun (UNIPMA) also issued a policy to conduct online learning in providing educational services. This research is descriptive qualitative because it is used to analyze the quality of learning in mathematics education study program through video-based eLMA. Data was collected by means of learning evaluation questionnaires and learning observations of basic mathematics studies, introduction to education, field geometry, and numerical methods. The Data analysis was carried out by reducing, presenting and drawing conclusions about the quality of learning in mathematics education study programs through video-based eLMA. The results of the study quality research showed that the results of the learning evaluation conducted by 4 lecturers who were in charge of basic mathematics studies, introduction to education, field geometry, and numerical methods were categorized as very good with successive scores of 3.65; 3.74; 3.64 and 3.68. The results of the observations of the internal quality assurance team also stated that the learning quality of the four courses was included in good criteria with recommendations maintained.